Analisis Tipe Perilaku Konsumen dalam Pembelian Salad Buah: Analisis Tipe Perilaku Konsumen dalam Pembelian Salad Buah - Setiyani, Rahmawati; Sepfrian, Bimoseno (Universitas Duta Bangsa Surakarta, 2025)
Indonesia is known as an agrarian country rich in biological resources, particularly in agriculture. One of Indonesia's natural riches is its wide variety of fruits. Fruits can be consumed directly or processed into various products. Currently, there has been a shift in consumer preferences toward imported fruits. In today’s digital era, consumer behavior has become increasingly dynamic due to the ease of access to vast and rapid information, making consumers more critical in comparing and considering products before making a purchase. Fruit salad has become one alternative to increase the consumption of local fruits in a more appealing way. The diversity of the population influences consumer behavior in purchasing fruit salad. The purpose of this study is to analyze the types of consumer behavior in purchasing fruit salad. The research used a descriptive-analytical method. A structured questionnaire was designed to identify consumer behavior types in buying fruit salad. The study was conducted in the city of Surakarta with a sample of 30 respondents. The results showed that the characteristics of fruit salad consumers are predominantly female, aged between 20 and 39 years, with a university-level education, working as private employees, and earning a monthly income of over IDR 3,000,000. The frequency of fruit salad consumption is mostly once a month, with consumption sizes ranging from 200 ml to 500 ml. Consumers enjoy the taste of fruit salad, thus the taste dimension is considered very pleasant. Consumers also pay attention to the packaging, which is seen as very attractive, and they prefer fruit salads with a variety of fruit fillings